2014
DOI: 10.1002/jmv.23893
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of GB virus type C among patients infected with HIV in Singapore

Abstract: Several studies have shown that individuals co-infected with GB virus type C (GBV-C), and human immunodeficiency virus (HIV) have slower progression to acquired immunodeficiency syndrome (AIDS) and a prolonged lifespan, compared to those infected with only HIV. In Singapore, despite the steadily increasing number of HIV infections in recent years, there are no studies documenting the extent of GBV-C/HIV co-infection in this group of patients. To fill this dearth of information, two GBV-C screening assays was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Multiple genotypes, namely 2, 3, 4, 7, and an unclassified group, were identified in this study; these findings differ from those of previous reports which suggest the predominance of genotype 3 in Beijing [ 35 ], and the Hubei province of China [ 6 ]. However, our results are consistent with observations in Singapore [ 36 ], and Indonesia [ 37 ] where high prevalence of HPgV-1 multiple genotypes have been described in patients with HIV-1 infection. These findings may be explained by the special geographic location of Yunnan province.…”
Section: Discussionsupporting
confidence: 93%
“…Multiple genotypes, namely 2, 3, 4, 7, and an unclassified group, were identified in this study; these findings differ from those of previous reports which suggest the predominance of genotype 3 in Beijing [ 35 ], and the Hubei province of China [ 6 ]. However, our results are consistent with observations in Singapore [ 36 ], and Indonesia [ 37 ] where high prevalence of HPgV-1 multiple genotypes have been described in patients with HIV-1 infection. These findings may be explained by the special geographic location of Yunnan province.…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of active HPgV infection in coinfected patients was 34% (118). This result was expected when observing the prevalence of HPgV RNA in HIV‐infected patients in different areas of the world, which ranges from 16.6% to 88.8% [Heringlake et al, ; Souza et al, ; Anggorowati et al, ; Lee et al, ; Sahni et al, ]. Other Brazilian studies found a similar prevalence of HPgV RNA in HIV‐1‐positive patients, estimated between 21% and 30% [Alcalde et al, ; Campos et al, ; Giret et al, ; Souza et al, ], but Southern Brazil may have slightly higher rates of coinfection when compared to the rest of the country.…”
Section: Discussionmentioning
confidence: 59%
“…Due to the similar modes of transmission, its prevalence increases in populations infected with HIV, HCV and those exposed to transfused blood products, transplanted patients, injecting drug users, hemophiliacs, and hemodialysis users [Mohr and Stapleton, ]. The worldwide prevalence of HPgV in HIV‐positive individuals varies between 17% and 89%, and it varies according to the region studied [Heringlake et al, ; Alcalde et al, ; Campos et al, ; Giret et al, ; Souza et al, ; Anggorowati et al, ; Ernst et al, ; Lee et al, ; Sahni et al, ]. In Brazil, the prevalence of HPgV RNA in HIV‐1‐positive patients has been estimated between 21% and 30% [Alcalde et al, ; Campos et al, ; Giret et al, ; Souza et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Recent taxonomic evolutions and proposals related to these single-stranded RNA viruses allow the current description of 11 species within the genus Pegivirus (Pegivirus A-K), the human and nonhuman primate pegivirus isolates being assigned to species Pegivirus C. 4 Despite a nonnegligible blood prevalence in healthy persons, that is 1% to 5% in developed countries and up to 20% in developing countries, and higher values in immunocompromised patients, both natural history and potential implication of pegiviruses in host's health are largely unknown despite their identification more than 20 years ago. [5][6][7][8][9][10][11][12][13][14] Of note, however, human immunodeficiency (HIV)-HPgV association studies were extensively explored, due to a possible beneficial effect in HIV infection motivating investigations about HIV-HPgV interactions at the molecular level. [15][16][17][18][19][20][21][22] Mechanisms of viral persistence and host-immune modulation remain also poorly characterized.…”
Section: Introductionmentioning
confidence: 99%